Zero tolerance for DWI arrestees reduces driver mortality: RAND. Issue 10 (3rd March 2023) - Knopf, Alison
Abstract : It is known that 24/7 sobriety — the abstinence requirement for people convicted of DWI, commonly known as zero tolerance — reduces re‐arrest, but until the release of a RAND report last week, the associations with improved health outcomes were not known. The study provides the first evidence that such programs, which include frequent alcohol testing and immediate punishment for violations, reduce mortality. However, there are variables in the magnitude of the improvements, probably based on whether participants received treatment or how they were selected for review — data to which the researchers did not have access. In addition, the approach by the researchers focused on individual‐level observables and selection, but not on variation in county‐level implementation or some other variables. In addition, the researchers could not assess the extent to which deterrence — the main tool of 24/7 sobriety programs — vs. other mechanisms drove the results. It's possible that the deterrence protocol in combination with other methods would be effective.